SIMPLIFYING POLYNOMIAL EXPRESSIONS IN FRACTIONS

Simplifying polynomial expressions is nothing but expressing the the rational expression to lowest term or simplest form.

The following steps ill be useful to simple rational expressions. 

Step 1 :

Factor both numerator and denominator, if it is possible.

Step 2 :

Identify the common factors in both numerator and denominator. 

Step 3 :

Remove the common factors found in both numerator and denominator.

Example 1 :

[(x- 2x)/(x + 2)] ⋅ [(3x + 6)/(x - 2)]

Solution :

Let f(x) = [(x- 2x)/(x + 2)] ⋅ [(3x + 6)/(x - 2)]

f(x) = [(x- 2x)/(x + 2)] ⋅ [(3x + 6)/(x - 2)]

f(x) = [x(x - 2)/(x + 2)] ⋅ [3(x + 2)/(x - 2)]

f(x) = 3x

So, the value of f(x) is 3x.

Example 2 :

[(x- 81)/(x- 4)]  [(x+ 6x + 8)/(x- 5x - 36)]

Solution :

Let f(x) = [(x- 81)/(x- 4)]  [(x+ 6x + 8)/(x- 5x - 36)]

x- 81 = x2- 92  ==> (x + 9)(x - 9)

x- 4 = x-  22  ==> (x + 2)(x - 2)

x+ 6x + 8 = (x + 2)(x + 4)

x- 5x - 36 = (x - 9)(x + 4)

f(x) = [(x + 9)( x - 9)/(x + 2)(x - 2)] ⋅ [(x + 2)(x + 4)/(x - 9)(x + 4)]

By simplifying (x + 9)/(x - 2)

So, the value of f(x) is (x + 9)/(x - 2).

Example 3 :

[(x- 3x - 10)/(x- x - 20)]  [(x- 2x + 4)/(x+ 8)]

Solution :

Let f(x) = [(x- 3x - 10)/(x- x - 20)]  [(x2-2x + 4)/(x+ 8)]

x- 3x - 10 = (x - 5)(x + 2)

x- x - 20 = (x - 5)(x + 4)

a+ b= (a + b)(a- ab + b2)

x+ 23 = (x + 2)(x- 2x + 4)

By applying the factors in f(x), we get

 =  [(x - 5)(x + 2)/(x - 5)(x + 4) [(x- 2x + 4)/(x + 2)(x2-2x + 4)]

=  1/(x + 4)

So, the value of f(x) is 1/(x + 4)

Example 4 :

[(x- 16)/(x2 - 3x + 2)]  [(x- 4)/(x+ 64)]  

[(x- 4x + 16)/(x- 2x - 8)]

Solution :

Let f(x) = [(x- 16)/(x2 - 3x + 2)]  [(x- 4)/(x+ 64)]  

[(x- 4x + 16)/(x- 2x - 8)]e

x- 16 = x- 4 ==> (x + 4)(x - 4)

x- 3x + 2 = (x - 1)(x - 2)

x- 4 = x- 22  ==> (x + 2)(x - 2)

x+ 64  = x+ 4 ==> (x + 4)(x- 4x + 16) 

x- 2x - 8 = (x - 4)(x + 2)

=  [(x+4)(x-4)/(x-1)(x-2)][(x+2)(x-2)/(x+4)(x2-4x+16)]

[(x2-4x+16)/(x-4)(x+2)]

f(x)  =  1/(x-1)

So, the value of f(x) is 1/(x-1).

Example 5 :

[(3x2+2x-1)/(x2-x-2)] [(2x2-3x-2)/(3x2+5x-2)]

Solution :

Let f(x)  =  [(3x2+2x-1)/(x2-x-2)]

 [(2x2-3x-2)/(3x2+5x-2)]

(3x2+2x-1)  =  (3x-1) (x+1)

(x2-x-2)  =  (x-2) (x+1)

(2x2-3x-2)  =  (2x+1) (x-2)

(3x2+5x-2) =   (2x-1) (x+2)

By applying the factors in f(x), we get

=  [(3x-1)(x+1)/(x-2) (x+1)][(2x+1) (x-2)/(2x-1) (x+2)]

=  (2x+1)/(x+2)

So, the value of f(x) is (2x+1)/(x+2).

Example 6 :

[(2x-1)/(x2+2x+4)] [(x4-8x)/(2x2+5x-3)] 

[(x+3)/(x2-2x)]

Solution :

Let f(x)  =  [(2x-1)/(x2+2x+4)] [(x4-8x)/(2x2+5x-3)] 

[(x+3)/(x2-2x)]

x4-8x  =  x(x3-23)

x4-8x  =  x(x-2)(x2+2x+4)

2x2+5x-3  =  (2x-1)(x+3)

x2-2x  =  x(x-2)

By applying the factors in f(x), we get

=  [(2x-1)/(x2+2x+4)][x(x-2)(x2+2x+4)/(2x-1)(x+3)] 

[(x+3)/x(x-2)]

=  1

So, the value of f(x) is 1.

Example 7 :

[(a+b)/(a-b)] [(a3-b3)/(a3+b3)]

Solution :

Let f(x)  =  [(a+b)/(a-b)] [(a3-b3)/(a3+b3)]

=  [(a+b)/(a-b)][(a-b)(a2+ab+b2)/(a+b) (a2-ab+b2)]

=  (a2+ab+b2)/(a2-ab+b2)

So, the value of f(x) is (a2+ab+b2)/(a2-ab+b2).

Example 8 :

[(x2-9y2)/(3x-3y)]  [(x2-y2)/(x2+4xy+3y2)]

Solution :

Let f(x)  =  [(x2-9y2)/(3x-3y)]  [(x2-y2)/(x2+4xy+3y2)]

x2-9y=  x2-(3y)2

x2-9y2  =  (x+3y)(x-3y)

3x-3y  =  3(x-y)

x2-y=  (x+y)(x-y)

x2+4xy+3y=  (x+3y)(x+y)

By applying the factors in f(x), we get

=  [(x+3y)(x-3y)/3(x-y)]⋅[(x+y)(x-y)/(x+3y)(x+y)]

By simplifying, we get

=  (x-3y)/3

So, the value of f(x) is (x-3y)/3.

Example 9 :

[(x2-4x-12)/(x2-3x-18)]  [(x2-2x-3)/(x2+3x+2)]

Solution :

Let f(x)  =  [(x2-4x-12)/(x2-3x-18)] 

 [(x2-2x-3)/(x2+3x+2)]

x- 4x - 12 = (x - 6)(x + 2)

x- 3x - 18 = (x - 6)(x + 3)

x- 2x - 3 = (x - 3)(x + 1)

x+ 3x + 2 = (x + 1)(x + 2)

f(x) = [(x - 6)(x + 2)/(x - 6)(x + 3)]⋅[(x - 3)(x + 1)/(x + 1)(x + 2)]

f(x) = (x - 3)/(x + 3)

So, the value of f(x) is (x - 3)/(x + 3).

Example 10 :

[(x2-3x-10)/(x2-x-20)][(x2-4x+16)/(x3+64)]

Solution :

Let f(x)  =  [(- 3x - 10)/(x- x - 20)][(x2- 4x + 16)/(x+ 64)]

x- 3x - 10 = (x - 5)(x + 2)

x- x - 20 = (x - 5)(x + 4)

x+ 43 = (x + 4)(x- 4x + 16)

By applying the factors in f(x), we get

f(x) = [(x - 5)(x + 2)/(x - 5)(x + 4)][(x- 4x + 16)/(x + 4)(x- 4x + 16)]

f(x) = (x + 2)/(x + 4)2

So, the value of f(x) is (x + 2)/(x + 4)2.

Example 11 :

 [(x2-16)/(x-2)] [(x2-4)/(x3+64)]

Solution :

Let f(x)  =  [(x2-16)/(x-2)] [(x2-4)/(x3+64)]

x2-16 = x- 42  ==> (x+4)(x-4)

x2-4  =  x- 22  ==> (x + 2)(x - 2)

x3+64  =  x+ 43 ==> (x + 4)(x- 4x + 16)

f(x) = [(x + 4)(x - 4)/(x - 2)] [(x + 2)(x - 2)/(x + 4)(x2- 4x + 16)]

f(x) = (x - 4)(x - 2)/(x- 4x + 16)

So, the value of f(x) is (x - 4)(x - 2)/(x- 4x + 16).

Example 12 :

[(x + 7)/(x+ 14x + 49)] [(x+ 8x + 7)/(x + 1)]

Solution :

Let f(x) = [(x + 7)/(x+ 14x + 49)] [(x+ 8x + 7)/(x + 1)]

x+ 14x + 49 = (x + 7)(x + 7)

x+ 8x + 7 = (x + 1)(x + 7)

By applying the factors in f(x), we get

f(x) = [(x + 7)/(x + 7)(x + 7)] [(x + 1)(x + 7)/(x + 1)]

f(x)  =  1

So, the value of f(x) is 1.

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Digital SAT Math Problems and Solutions (Part - 106)

    Feb 04, 25 08:16 AM

    digitalsatmath107.png
    Digital SAT Math Problems and Solutions (Part - 106)

    Read More

  2. SAT Math Resources (Videos, Concepts, Worksheets and More)

    Feb 04, 25 08:15 AM

    SAT Math Resources (Videos, Concepts, Worksheets and More)

    Read More

  3. Digital SAT Math Problems and Solutions (Part - 107)

    Feb 04, 25 08:11 AM

    digitalsatmath108.png
    Digital SAT Math Problems and Solutions (Part - 107)

    Read More